Promoting the Open Science culture in university libraries of developing countries: case studies of the French-speaking universities of Belgium cooperation programs in the Global South - Brodkom, Frédéric; Pochet, Bernard (Septentrio Conference Series, 2017)
Watch the VIDEO here. Presenter - Frédéric Brodkom. The ARES-CCD (formerly CUD) is the French-speaking universities and high-school of Belgium Commission for the Cooperation to Development. With an annual budget of 31 M€ fully dedicated to the academic development of actually 19 universities of North and Central Africa, South-East Asia, Western South America and Greater Antilles, this commission brings together volunteers of the academic, scientific and administrative staffs of our universities. Since 2000, librarians are strongly involved in this project with the aim to develop the partner’s libraries, to improve their infrastructures and operations, to facilitate their access to documentary resources and to strengthen their librarians' skills. Given the important documentary needs of students and researchers in the South and the lack of financial resources, the promotion of Open Science is more than an obvious. We will show that, in addition to our activities of purchasing books or materials, basic training or library renovation, we develop, in close partnership with our colleagues, the Open Science culture in six fields: (1) The installation and support of open-source ILS (mainly KOHA and PMB), including the learning of IT teams (2) The harvesting and promotion of OA resources via our Web Portal, including subscription to official resources of international organization (3) The development of policies to develop local institutional repositories for new and archived (printed) publications and thesis (DSpace support, purchase of scanner, etc) (4) The support to the development of university presses to reduce/abolish the excessive cost of printed course materials for students (5) Training and awareness-raising of library trainers for academic social networks, data exchange platforms, community-based researchers' sites, OA use, etc. (6) Promote the obligation to deposit in our university repositories the scientific papers financed by the ARES-CCD cooperation and co-signed by Belgian researchers and partners of developing countries (academic and doctorate students). Concrete case studies of our 17 years of experience in the South from Haiti to Vietnam will illustrate these actions. Perspectives on future projects will also be discussed, such as a week, jointly with all our partners, of exchange and work in Belgium in 2018 (as already done in 2016) on the topic of the practical implementation of Open Access in their universities. <!–[if gte mso 9]> Normal 0 21 false false false NO-BOK X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>